The report of Pedro Varaez about the profession of midwife and the answer of Francisco Antonio Díez de Cabrera - Rafaela González Castrillo; Ricardo González Castrillo (Universidad de Alicante, 2015)
Objetive: To provide information on the vision of the office of midwife in the Spain of the sixteenth and seventeenth centuries. To describe the different positions in relation to the practice of this activity in this historical centuries. Method: Detailed analysis of the information on this subject that it's included in an unpublished manuscript preserved in the Royal Library of Madrid. An interesting unpublished manuscript preserved in the Royal Library in Madrid provides information on the profession of midwife. It has two distinct parts. The first part includes the report that drafted the lawyer Pedro Varaez in order to show that children of mothers who practiced this profession didn't lose their privileges in case of having by birth. In his presentation, collects quotes from the sacred books, the works of classical authors and, above all, expert medieval canonists and different jurists of the sixteenth and seventeenth centuries. The second, written by Antonio Diez also licensed Francisco Cabrera, rejected every argument put forward by Varaez, but without mentioning hardly more than a few references. The document also contains interesting information for the history of the profession of midwife and recognition they enjoyed in different periods, as people who ensured the health of women in labor, staking his entire practice, and whose presence was relevant when to guarantee the rights of the firstborn, in case of multiple births.